Wilcoxon Analysis to Compare the Open Unemployment Rate Before and After the Implementation of ASEAN Economic Community (EAC) In Indonesia - Novalia, Novalia; Nur’aeni, Nur’aeni; Purnama, Husna; Indriyani, Indriyani (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
The implementation of the EAC should be seen positively since it opens the opportunities for job seekers in Indonesia to have a career abroad. With varied employment opportunities, it is expected that the open unemployment rate in Indonesia will decline. The purpose of this study is to compare the level of open unemployment rate in Indonesia before and after the implementation of the ASEAN Economic Community (EAC) using Wilcoxon Analysis. This research is quantitative. Wilcoxon analysis is used to compare the open unemployment rate in Indonesia before and after the EAC is implemented. The result shows that there is no significant difference between the average open unemployment rate before and after the implementation of EAC.